The Effects Macroeconomic on Corporate Sukuk Ijarah Returns: Evidence from Indonesia - Rani, Lina Nugraha; Laila, Nisful; Rahman, Asmak Ab; Bayuny, Ahmad Fadlur Rahman; Filianti, Dian; Purbasari, Lintang Titian (Migration Letters, 2024)
The study examines Inflation, BI Rate, Exchange Rate, and Gross Domestic Product (GDP) on Corporate Sukuk Ijarah Returns. The study uses a quantitative approach, and the data used is secondary data from 4 companies issuing sukuk ijarah, which are registered with the Financial Services Authority (OJK) and sourced from the websites of each company. This study uses data analysis techniques, namely the General Method of Moment (GMM). The findings of this study showed that inflation and the Exchange Rate do not affect Corporate Sukuk Ijarah Returns. However, the BI Rate and Gross Domestic Product (GDP) influence Corporate Sukuk Ijarah Returns. Increased economic activity in the real sector means a positive response to the market. It will encourage public demand for sukuk and may cause the price of sukuk to rise. When the price of sukuk increases, the company will set a high sukuk yield so investors can invest their funds. This study broadens our understanding of the impact of Inflation, BI Rate, Exchange Rate, and Gross Domestic Product (GDP) on Corporate Sukuk Ijarah Returns.